School-based management: A model of implementation for Malaysian primary schools - Abdul Samad, R.S.; Idris, A.R. (2008)
School-based management (SBM, defined as the decentralization of decision-making authority to the school site, is one of the most popular strategies that came out of the 1980s school reform movement. Over the past decade, many school districts have implemented this method of managing school budget, curriculum, and personnel decisions. It attempts to give school constituents administrators, teachers, parents, and other community members more control over what happens in schools. The foundation of school-based management is the concept of decentralized management, which has a longer history in the private sector. Studies of decentralization in the private sector suggest that high-involvement management is most appropriate in organizations where the work is complex, such as teaching in schools: is best done collegially or in teams; involves uncertainty in its day-to day tasks; and exists in a rapidly changing environment. Research on the private sector also points out that control over four resources, namely power, knowledge, information, and rewards needs be decentralized throughout the organization in order to maximize performance improvement. A study is being conducted on the implementation of school-based management in Malaysian primary schools, with particular focus on five major domains of school-based management: understanding about SBM; organizational dimensions; school leadership and strategy; decision-making; and effective implementation. A survey was administered to primary school headmasters to collect data on the five domains. Data were analyzed using structural equation modelling (SEM) and the research is expected to produce an SBM model that is appropriate for managing Malaysian primary schools.